2019
DOI: 10.1007/s42452-019-0893-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/zeolite nano-composite hydrogels as promising water reservoir materials: effect of clinoptilolite content on physicochemical properties

Abstract: In this work, with the aim of improving the water uptake behavior and mechanical properties, a novel nano-composite hydrogel system was synthesized using clinoptilolite as a semi-layered zeolite. Accordingly, the gelatin/SCMC-g-poly (AA-co-AAm)/clinoptilolite semi-IPN nano-composite hydrogel samples were synthesized and studied. The FTIR, XRD, SEM and EDX analysis were accomplished to confirm the successful synthesis of the nano-composite hydrogel samples. Additionally, to investigate the effect of clinoptilol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…So, it can be said that the process of loading nutrients into the hydrogel network was successful. Some studies found results of a similar nature (Olad et al, 2019;Dos Santos Pereira et al, 2020;Kenawy et al, 2020;Salimi et al, 2020;Pimsen et al, 2021;Mohamed et al, 2022).…”
mentioning
confidence: 89%
“…So, it can be said that the process of loading nutrients into the hydrogel network was successful. Some studies found results of a similar nature (Olad et al, 2019;Dos Santos Pereira et al, 2020;Kenawy et al, 2020;Salimi et al, 2020;Pimsen et al, 2021;Mohamed et al, 2022).…”
mentioning
confidence: 89%
“…The dependence of the swelling of "alkaline" (1) and "acid" (2) gelatin in water with pH [5]: ∆m -mass gain Природные цеолиты эффективно применяются в ветеринарии для профилактики и лечения незаразных болезней, кожных заболеваний [8], в медицине -для лечения гнойных ран и ожогов [9]. Нетоксичный, доступный и недорогой природный цеолит -клиноптилолит является перспективным наполнителем модифицированных желатиновых пленок [3,[10][11][12]. Наличие в клиноптилолите поверхностных силанольных (≡Si-OH) групп, способных к электростатическому взаимодействию с положительно заряженными участками макромолекул желатина и к образованию межмолекулярных водородных связей с карбоксильными или аминогруппами [7] непосредственно, либо через прослойку молекул воды, позволяет рассматривать возможность дополнительного усиления структуры.…”
Section: Introductionunclassified